Review Deskriptif Buku Psikologi Kepribadian: Teori dan Penelitian Edisi Kesembilan Lawrence A. Pervin, Daniel Cervone, dan Oliver P. John - Nurhamidah, Nurhamidah; Yustiana, Yusi Riksa (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This descriptive review examines the book "Personality Psychology: Theory and Research" ninth edition by Lawrence A. Pervin, Daniel Cervone, and Oliver P. John, published by Kencana Prenada Media Group (2012). The purpose of this review is to provide a comprehensive overview of the book's structure, content, and contributions to personality psychology literature, as well as to evaluate its relevance for education and practice in guidance and counseling. Analysis reveals that this book successfully presents a broad panorama of personality theories—from classical psychodynamic to contemporary neuroscience—with an objective and balanced approach. The book's main strengths lie in its organic integration of theory and empirical research, accessible yet rigorous writing style, and pedagogical features that support deep learning. The book includes comprehensive discussions of psychodynamic theory, trait approaches (including the Big Five model), humanistic perspectives, social-cognitive theory, as well as biological and genetic foundations of personality. The ninth edition introduces significant expansion in personality neuroscience and contextual perspectives that reflect current developments in the field. For students and practitioners of guidance and counseling, this book offers an essential theoretical foundation for understanding clients holistically, conducting valid assessments, and selecting theoretically grounded interventions. Despite limitations regarding the depth of certain topics and cultural bias, the book's strengths far outweigh its weaknesses. This review recommends the book as a primary textbook for personality psychology courses and as an important reference for counseling practitioners.   Review deskriptif ini mengkaji buku "Psikologi Kepribadian: Teori dan Penelitian" edisi kesembilan karya Lawrence A. Pervin, Daniel Cervone, dan Oliver P. John yang diterbitkan oleh Kencana Prenada Media Group (2012). Tujuan review adalah memberikan gambaran komprehensif tentang struktur, konten, dan kontribusi buku terhadap literatur psikologi kepribadian, serta mengevaluasi relevansinya untuk pendidikan dan praktik bimbingan dan konseling. Analisis menunjukkan bahwa buku ini berhasil menyajikan panorama luas teori kepribadian—dari psikodinamik klasik hingga neuroscience kontemporer—dengan pendekatan yang objektif dan berimbang. Kekuatan utama buku terletak pada integrasi organik antara teori dan penelitian empiris, gaya penulisan yang accessible namun rigorous, serta fitur pedagogis yang mendukung pembelajaran mendalam. Buku ini mencakup pembahasan komprehensif tentang teori psikodinamik, trait (termasuk model Big Five), humanistik, kognitif-sosial, serta dasar biologis dan genetik kepribadian. Edisi kesembilan memperkenalkan ekspansi signifikan dalam neuroscience kepribadian dan perspektif kontekstual yang mencerminkan perkembangan terkini dalam field. Untuk mahasiswa dan praktisi bimbingan dan konseling, buku ini menawarkan foundation teoretis yang essential untuk memahami klien secara holistik, melakukan assessment yang valid, dan memilih intervensi yang theoretically grounded. Meskipun memiliki keterbatasan terkait kedalaman pembahasan topik tertentu dan bias kultural, kekuatan buku jauh melebihi kelemahannya. Review ini merekomendasikan buku sebagai textbook utama untuk mata kuliah psikologi kepribadian dan sebagai referensi penting untuk praktisi konseling.